Influence of Wear-Induced Turning on the Roll’s Fatigue Life - Francisko Lukša; Željko Domazet; Đorđe Dobrota; Branko Lalić (Metals)
Friction-induced wear during the rolling process needs periodic remachining of caliber roll grooves, which increases operational costs and reduces roll fatigue life. Stress analysis showed that a regular reduction in the initial diameter by up to 3.5% results in a 12.2% increase in maximum stress amplitude, reducing the estimated fatigue life by a factor of 1.5. Although fatigue life is reduced, the risk of failure under normal operating conditions remains low. Further analysis, considering mill design and roll hardness, demonstrated the feasibility of additional roll diameter reduction, thereby enabling increased production using the same rolls. The findings support further diameter reduction without compromising performance and underscore the importance of integrating such analysis into the roller design process to optimize fatigue life and roll utilization.